Mucinous cystic neoplasms of the pancreas demonstrate in situ production of estrogen - Kim, Jinyong; Chandrasekar, Aswath P.; Van Treeck, Benjamin J.; Olave, Maria C.; Shahi, Maryam; Moreira, Roger K.; Byeon, Seul Kee; Sachdeva, Gunveen S.; Juskewitch, Justin E.; Bakkum-Gamez, Jamie N.; Kaufmann, Scott H.; Lee, Sun-Hee; et al. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMucinous cystic neoplasms (MCNs) are rare cystic tumors that may occur in the liver, pancreas, or retroperitoneum, defined histologically by the presence of an “ovarian type stroma.” While this morphology has been well characterized, it remains unknown whether the tumor stroma is functionally active. In our current study, we describe the detection of estrogen and its metabolites in the ovarian-type stroma of MCN tumors of the pancreas.MethodsUsing a novel liquid chromatography-tandem mass spectrometry (LC-MS/MS) technique. We performed LC-MS/MS on 14 cases of MCN, with and without dysplasia, following macro dissection from formalin fixed tissue.ResultsWe identified that relative to histologically normal pancreas, and intraductal papillary mucinous neoplasm (IPMN), the stroma in MCN expresses significantly greater levels of estrone (E1), estradiol (E2), estriol (E3), 2-hydroxyestradiol (2-OHE2), 2-methoxyestrone (2-MeOE1), 2-methoxyestradiol (2-MeOE2) and 16α-hydroxyestrone (16α-OHE1), at levels similar to those seen in the stroma in the normal ovary.DiscussionThese findings establish the functional capability of the ova rian-type stroma in MCN tumors for endogenous hormone production and show that the levels of estrogen in the stroma of MCN tumors approach those of the ovary. These findings serve as a basis for future studies examining the systemic effects of estrogen and the effects of estrogen on tumor progression, both in MCN tumors and tumor metastatic to the ovary.